2010
DOI: 10.1111/j.1475-2743.2010.00266.x
|View full text |Cite
|
Sign up to set email alerts
|

Soil tillage methods to control phosphorus loss and potential side-effects: a Scandinavian review

Abstract: In Scandinavia high losses of soil and particulate‐bound phosphorus (PP) have been shown to occur from tine‐cultivated and mouldboard‐ploughed soils in clay soil areas, especially in relatively warm, wet winters. The omission in the autumn of primary tillage (not ploughing) and the maintenance of a continuous crop cover are generally used to control soil erosion. In Norway, ploughing and shallow cultivation of sloping fields in spring instead of ploughing in autumn have been shown to reduce particle transport … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
77
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(85 citation statements)
references
References 54 publications
(111 reference statements)
6
77
1
Order By: Relevance
“…Gaynor and Findlay (1995) concluded that conservation tillage reduces average soil loss compared to conventional tillage. The same authors concluded that conservation tillage has effectively reduced soil erosion but also increased phosphorus loss, a finding in opposition to the results obtained by Ulen et al (2010). Hussain et al (1999) determined that soil pH and TOC were higher at NT compared to conventional tillage.…”
Section: Resultscontrasting
confidence: 52%
“…Gaynor and Findlay (1995) concluded that conservation tillage reduces average soil loss compared to conventional tillage. The same authors concluded that conservation tillage has effectively reduced soil erosion but also increased phosphorus loss, a finding in opposition to the results obtained by Ulen et al (2010). Hussain et al (1999) determined that soil pH and TOC were higher at NT compared to conventional tillage.…”
Section: Resultscontrasting
confidence: 52%
“…In Scandinavia leaf net blotch (Pyrenophoros teres) has increased after no-till (Ulén et al 2010) but generally increased crop diseases have not been widespread with no-till. In Scotland fungus snow-rot (Typhula), which affects winter-sown cereals, was less prevalent after no-till than after ploughing (Ball and Davies, 1997).…”
Section: Crop Diseasesmentioning
confidence: 99%
“…Conservation tillage in autumn may reduce losses of soil and PP by improving soil structure. In Norway, ploughing and shallow cultivation of sloping fi elds in spring instead of ploughing in autumn have been shown to reduce particle transport by up to 89% on highly erodible soils (Ulén et al 2010). Rational land-use policies, such as the promotion of 'set-aside' on erodible soils, the use of grass strips on erodible arable slopes and buffer strips in riparian zones, were identifi ed as mitigation options for reducing soil erosion by Fullen et al (2003).…”
Section: Mitigation Measures To Prevent Erosion On Tillage Soilsmentioning
confidence: 99%